El dividendo obligatorio regulado por el artículo 231 de la ley general de sociedades - Ossio Gargurevich, Jorge (Pontificia Universidad Católica del Perú, 2016)
Article 231 of the Peruvian Corporations Act states that, if shareholders that have at least 20% of the voting shares of a company request a distribution of a determined amount of utilities from the previous period, if there are distributable utilities, the company is obligated to distribute them.The author of the present article analyses the convenience of this disposition, from the point of view of the actors involved and taking into account the experience in other countries regarding regulation about the mandatory dividend.Furthermore, the author explains the practical application of article 231, and he inquires and questions the interpretation that has to be given as to allow the disposition to fulfill its objectives.

El artículo 231 de la Ley General de Sociedades señala que, si los accionistas que ostentan el 20% de las acciones con derecho a voto solicitan una distribución de determinado monto de las utilidades, siempre que haya utilidades distribuibles, la sociedad está obligada a repartir las mismas. El autor del presente artículo analiza la conveniencia de la mencionada norma, desde el punto de vista de los actores involucrados y teniendo en cuenta la regulación sobre el dividendo mínimo en otros países. Asimismo, el autor explica la aplicación del artículo en la práctica, y se pregunta y cuestiona sobre el sentido que se le debe dar para que no se desvirtúe su finalidad.
The mandatory dividend regulated by article 231 of the Peruvian corporations act
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01